The Utilization of Artificial Intelligence in English Language Learning in the Nahdlatul Wathan Environment - Sudiani; Herman Zuhdi; Muhammad Salim (CV. Yazri Aksara Nusantara, 2026)
The rapid development of artificial intelligence has transformed various aspects of education, including English language teaching. This study aims to describe the utilization of artificial intelligence in English language teaching within the Nahdlatul Wathan educational environment, examine teachers’ perceptions of its use, and identify the supporting factors, challenges, and future opportunities associated with its implementation. A qualitative approach with a case study design was employed in three Nahdlatul Wathan secondary schools, namely SMAS NW Pendem, SMK NW Janapria, and MAS NW Lengarak, located in Janapria District, Central Lombok Regency. The participants consisted of three English teachers and two school leaders selected through purposive sampling. Data were collected through semi-structured interviews, observations, and document analysis and were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that artificial intelligence is primarily utilized as a supporting tool for developing instructional materials, designing assessments, enhancing vocabulary and grammar instruction, and assisting writing activities. Teachers generally expressed positive perceptions of AI while emphasizing the need for information verification and responsible use. The study suggests that artificial intelligence can support innovation in English language teaching when integrated critically, ethically, and under the guidance of teachers as the primary actors in the educational process.Perkembangan kecerdasan artifisial telah mendorong perubahan dalam berbagai aspek pendidikan, termasuk pembelajaran Bahasa Inggris. Penelitian ini bertujuan untuk mendeskripsikan pemanfaatan kecerdasan artifisial dalam pembelajaran Bahasa Inggris di lingkungan Nahdlatul Wathan, menganalisis persepsi guru terhadap penggunaannya, serta mengidentifikasi faktor pendukung, penghambat, dan peluang pengembangannya. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus yang dilakukan pada SMAS NW Pendem, SMK NW Janapria, dan MAS NW Lengarak di Kecamatan Janapria, Kabupaten Lombok Tengah. Informan penelitian terdiri atas tiga guru Bahasa Inggris dan dua informan dari unsur pimpinan sekolah yang dipilih secara purposif. Data dikumpulkan melalui wawancara semi-terstruktur, observasi, dan dokumentasi, kemudian dianalisis menggunakan model Miles, Huberman, dan Saldaña. Hasil penelitian menunjukkan bahwa kecerdasan artifisial dimanfaatkan sebagai alat bantu dalam penyusunan materi, pembuatan evaluasi, pengembangan kosakata dan tata bahasa, serta pendampingan keterampilan menulis. Guru memiliki persepsi yang positif terhadap penggunaan AI, meskipun tetap menyoroti pentingnya verifikasi informasi dan pengawasan terhadap penggunaannya. Temuan ini menegaskan bahwa AI berpotensi mendukung inovasi pembelajaran Bahasa Inggris apabila diintegrasikan secara kritis, etis, dan tetap menempatkan guru sebagai aktor utama dalam proses pendidikan.